MENINGKATKAN HASIL BELAJAR TENTANG PENGURANGAN DUA BILANGAN DENGAN MENERAPKAN MODEL PEMBELAJARAN THINK PAIR SHARE BAGI SISWA KELAS 1 MI - SUSANTI SUSANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to improve learning outcomes Mathematics. Mathematics as a compulsory subject that must be taken by students. In carrying out learning in class, especially learning mathematics about subtracting two numbers which is carried out in class 1 MI Nahdlatussubban in semester 1 of the 2021/2022 academic year, the author feels that there are deficiencies that occur in learning outcomes. The test scores obtained by students were still below the KKM, the specified KKM was 70 while the class average was 63. Out of 30 students only 12 or 40% of students had experienced completeness and 18 or 60% of students had not yet experienced completeness. Based on the results of the analysis carried out by the Class 1 teacher, the learning activities that have been carried out in the Mathematics subject about subtracting two-digit numbers with low learning outcomes. The cause of failure in learning is that the teacher still applies conventional learning models, the teacher does not give students the opportunity to ask questions, rarely uses props, and is too fast in explaining, so that students tend to be passive and not focus on following the lesson. Concepts in mathematics are abstract, whereas in general SD/MI level students still think from concrete things to abstract things. In order to overcome this problem, the author will try to use the TPS (Think Pair Share) learning model and use visual aids. The TPS learning model is a cooperative learning model designed to influence student interaction patterns. TPS is an effective way to vary the atmosphere in class discussion patterns. In addition TPS can give students a lot of time to think, to respond and to help. The use of the TPS (Think Pair Share) Learning Model can improve Mathematics learning outcomes for Class 1 students of MI Nahdlatussubban Karangtengah Demak District, this is evidenced by an increase in learning outcomes for the initial condition of the class average of only 63, in cycle 1 the class average of 72 means an increase of around 9 points. Meanwhile, in cycle 2 to 85, it increased by around 13 points. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar Matematika. Matematika sebagai mata pelajaran wajib yang harus ditempuh siswa. Dalam melaksanakan pembelajaran di kelas, terutama pembelajaran matematika tentang pengurangan dua bilangan yang dilakukan di kelas 1 MI Nahdlatussubban pada semester 1 tahun pelajaran 2021/2022, penulis merasakan ada kekurangan yang terjadi dalam hasil pembelajaran. Nilai ulangan yang diperoleh siswa masih di bawah KKM, KKM yang ditentukan adalah 70 sedangkan rerata kelas adalah 63. Dari 30 siswa hanya 12 atau 40% siswa yang sudah mengalami ketuntasan dan 18 atau 60% siswa belum mengalami ketuntasan. Berdasarkan hasil analisis yang dilakukan oleh guru Kelas 1, maka kegiatan pembelajaran yang telah dilakukan pada mata pelajaran Matematika tentang pengurangan bilangan dua bilangan dengan hasil belajar masih rendah. Adapun penyebab kegagalan dalam pembelajaran adalah guru masih menerapkan model pembelajaran konvensional, guru tidak memberi kesempatan siswa untuk bertanya, jarang menggunakan alat peraga, dan terlalu cepat dalam menerangkan, sehingga siswa cenderung pasif dan tidak fokus dalam mengikuti pelajaran. Konsep dalam Matematika abstrak, sedangkan pada umumnya siswa jenjang SD/MI masih berpikir dari hal-hal yang konkret menuju hal-hal yang abstrak. Guna mengatasi masalah tersebut, penulis akan mencoba menggunakan model pembelajaran TPS (Think Pair Share) dan menggunakan alat peraga. Model pembelajaran TPS adalah salah satu model pembelajaran kooperatif yang dirancang untuk mempengaruhi pola interaksi siswa. TPS merupakan suatu cara yang efektif untuk membuat variasi suasana pola diskusi di kelas. Selain itu TPS dapat memberi banyak waktu siswa untuk berpikir, untuk merespon dan untuk membantu. Penggunaan Model Pembelajaran TPS (Think Pair Share) dapat meningkatkan hasil belajar Matematika siswa Kelas 1 MI Nahdlatussubban Kecamatan Karangtengah Demak, hal ini dibuktikan terjadi peningkatan hasil belajar kondisi awal rerata kelas hanya 63 , pada siklus 1 rerata kelas 72 berarti mengalami kenaikan sekitar 9 poin. Sedangkan pada siklus 2 menjadi 85 mengalami kenaikan sekitar 13 poin.